A prospective feasibility study to differentiate sacral neuromodulation lead electrode configurations using motor and sensory thresholds and locations of sensation - Tianyu He; Christopher Hornung; Michael D. Evans; Stephanie J. Zoghbi; Leya A. Chahine; Fatima A. Nazar; Dwight E. Nelson; Nissrine Nakib (BMC Urology)
Abstract Background Accurate positioning and programming of sacral neuromodulation (SNM) relies upon the use of several intraoperative and postoperative stimulation measurements. While the clinical utility of these acute measurements including pelvic floor motor thresholds (PFMT), toe/leg motor thresholds (TMT), and sensory thresholds (ST), are widely accepted, their usefulness in quantitative research remains unclear. The purpose of this prospective study was to test these measurements and gauge their utility in future research. Methods Eight participants received Axonics SNM, 6 Medtronic Interstim II, and 2 Medtronic Micro SNM. PFMT was measured after implantation. ST and the location of sensation (LOS) were measured immediately postoperatively (PO), at pre-release from the surgery center (PR), and during a follow-up clinic visit (FU). Thresholds were compared across contact and time using linear mixed-effects models. Results Significant differences in PFMT were found across electrode configurations, with stimulation through proximal contacts exhibiting lower PFMT than distal configurations. ST displayed no significant differences across electrodes and showed minimal changes over time. LOS exhibited substantial variability across patients and periods. Conclusions Results suggest that PFMT were able to differentiate differences across electrode configurations that may be useful for future quantitative research. The lack of differences in ST and LOS across electrode configurations was interesting given the focus on these measurements clinically. Future testing is to confirm these limitations.